2007
DOI: 10.1063/1.2405738
|View full text |Cite
|
Sign up to set email alerts
|

Gain in p-doped quantum dot lasers

Abstract: We directly measure the gain and threshold characteristics of three quantum dot laser structures that are identical except for the level of modulation doping. The maximum modal gain increases at fixed quasi-Fermi level separation as the nominal number of acceptors increases from 0 to 15 to 50 per dot. These results are consistent with a simple model where the available electrons and holes are distributed over the dot, wetting layer, and quantum well states according to Fermi-Dirac statistics. The nonradiative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…This implies that the QD laser can be driven harder before the gain switches from GS to ES in the presence of doping [2]. One observes that the ES gain in I_as, I_650, and P_650 reaches its maximum value just around the point that GS gain starts to decrease, showing that the GS and ES transitions compete for the same carriers [5].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This implies that the QD laser can be driven harder before the gain switches from GS to ES in the presence of doping [2]. One observes that the ES gain in I_as, I_650, and P_650 reaches its maximum value just around the point that GS gain starts to decrease, showing that the GS and ES transitions compete for the same carriers [5].…”
Section: Resultsmentioning
confidence: 91%
“…Rapid thermal annealing (RTA) and p-doping are two methods that are commonly used to improve the performances of QD lasers. For example, RTA process improves the dynamic characteristics [6], while p-doping improves the lasing gain and temperature sensitivity [2], [3]. In addition, since RTA process might result in the intermixing of the QD with the surrounding matrix, the difference between the interlevel energy is expected to be lower.…”
Section: Introductionmentioning
confidence: 98%
“…The GS-ES separation was found to be 50 meV, which is less than that found for InAs QDs emitting at 1.3 lm, where the separation is typically 60-80 meV. 2 The inhomogeneous broadening (determined by fitting a Gaussian function to the GS absorption), has a value (r) of 24 meV compared to, for example, a GS broadening of 30 meV as previously determined for InAs QDs. 4 Samples were fabricated into 50 lm wide oxide-isolated stripe multi-section test structures and lasers.…”
mentioning
confidence: 89%
“…However, it is also observed that the temperature dependence of the threshold current often has a local minimum in the region 100 K to 200 K rather than a monotonic decrease with decreasing temperature and this phenomenon has been ascribed to the breakdown of thermal equilibrium conditions at low temperatures which cannot be described by Fermi Dirac statistics 2 nor account for two state lasing. The breakdown of thermal equilibrium seems to occur particularly in p-doped devices due, it is supposed, to a breakdown of the thermal coupling between electron states and the wetting layer even around room temperature, due to the lowering of the Fermi levels 3 .…”
Section: Introductionmentioning
confidence: 99%